Cervical squamous cell carcinoma of unknown primary: Oncological outcomes and prognostic factors - Meulemans, Jeroen; Voortmans, Jens; Nuyts, Sandra; Daisne, Jean-François; Clement, Paul; Laenen, Annouschka; Delaere, Pierre; Van Lierde, Charlotte; Poorten, Vincent Vander (Frontiers in Oncology, 2022)
Background/ Objectives: Cervical squamous cell carcinoma of unknown primary (SCCUP) is a rare entity within head and neck cancer and both treatment regimens as well as identified potential predictors for oncological outcomes vary between published series. In this study, we evaluated oncological outcomes and identified potential prognostic factors for outcome. Patients and Methods: This retrospective monocentric cohort study includes 82 SCCUP patients diagnosed and treated between January 2000 and June 2021. Overall survival (OS), disease-specific survival (DSS), disease-free survival (DFS) and locoregional recurrence-free survival (LRFS) were evaluated. The Cox proportional hazards model was used to analyze the prognostic effect of patient and tumor characteristics on oncological outcomes. Results: Five year OS, DSS, DFS and LRFS were respectively 53.9%, 72.2%, 68.9% and 67.3%. The p16 status was evaluated in 55 patients with 40% being p16 positive. On univariable analysis, p16 negative SCCUPs had significantly worse survival and recurrence rates in the presence of clinical extranodal extension (cENE) (OS: p=0.0013, DSS: p=0.0099, DFS: p=0.0164, LRFS: p=0.0099) and radiological extranodal extension (rENE) (OS: p=0.0034, DSS: p=0.0137, DFS: p=0.0167, LRFS: p=0.0100). In p16 positive SCCUP patients, rENE had a significantly negative prognostic effect on DFS (p=0.0345) and LRFS (p=0.0367). Total group multivariate analysis identified rENE as an independent negative predictor for all oncological outcomes. The “number of positive lymph nodes” was a second independent predictor for DSS (p=0.0257) and DFS (p=0.0435). Conclusions: We report favorable oncological outcomes, comparable to previously published results. Although the presence of rENE seems associated with poor oncological outcomes, the differential effect of clinical, radiological and pathological ENE in both p16 positive and negative subgroups remain to be elucidated by further prospective research.